Tracking the morphological diversity of Bucephalandra motleyana Schott (1858 (Araceae) using its commercial name in the proximities of Jakarta, Indonesia - Media Fitri Isma Nugraha; Ina Erlinawati; Deni Sahroni; Wening Enggarini; Rossa Yunita; Muhammad Yamin (Jurnal Biologi Universitas Andalas, 2020)
Bucephalandra Schott, Gen. Aroid. (1858) is a genus within Araceae family and assigned to some aquatic plants endemic to Borneo Island, currently representing 31 species. Bucephalandra species are known as ornamental aquatic plants and common for aquascaping. These aquatic plants are highly valued, approximately € 300 in European ornamental aquatic markets and Rp 50,000–700,000 in local markets. We collected 195 specimens of Bucephalandra from 5 ornamental aquatic plant markets in the proximity of Jakarta City, Indonesia. This study is based on repeated confusion with overwhelmed vernacular names assigned for Bucephalandra in the markets. Therefore, the aims of this study are to collect and to identify of Bucephalandra offered in the aquatic plant markets with emphasis on Bucephalandra motleyana Schott 1858. Specimen identification are mostly based on reference specimens stored in the Herbarium Bogoriense Botany Division – Research Centre for Biology – Indonesian Institute of Sciences (LIPI) Cibinong. As result, this study collected 110 specimens belonged to Bucephalandra motleyana Schott 1858 and 85 specimens identified as other species within this genus.